Open education practices: a meta-synthesis of literature - Shareefa, Mariyam; Moosa, Visal; Hammad, Aaida; Zuhudha, Aminath; Wider, Walton (Frontiers in Education, 2023)
Most of the recent reviews of literature on open education practises (OEP) seem to be limited in their scope, inhibiting their capacity to arrive at a comprehensive understanding of the concept of OEP. Hence, this systematic literature review was conducted with the purpose of analysing past research on OEP in an effort to identify how OEP is theorised and defined in the existing literature.Employing a systematic protocol, the literature search was conducted using the Dimensions database. A total of 30 publications were considered for the qualitative analysis, which engaged a thematic approach. The findings indicated that the concept of OEP can be explained with a combination of three major components: open education resources, an open teaching and learning process, and open research and scholarly practice. The findings also showed that these components should be grounded in six principles: accessibility, flexibility, shareability, affordability, innovation, and academic freedom. The findings imply that, in order to meaningfully execute open education practices, each of the three components must be given equal importance and that these practices be well grounded in the identified six principles.